Meanings of Quebec’s Linguistic Integration Program as Perceived by Recent Immigrants: Education, Socialization, Encouragement, and Personal Development Through Language Courses - Zagrebina, Anna (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
The meanings and effects of government-funded language training programs is an important research subject because it concerns possible prejudices against immigrants and negative stereotypes as well as discussions on the effectiveness of immigrant integration policies in general. The effects of civic integration programs are difficult to measure, and there is insufficient research devoted to such analysis. This study, by applying quantitative content analysis to examine the responses of 73 participants in a linguistic integration program, found the most essential meanings of the program that can be revealed only through personal participation. The results of this study can be used to evaluate language training programs for adult newcomers and provide ideas on which elements of the educational process should receive special attention from teachers and employers of language programs.